2021
DOI: 10.1080/13218719.2020.1821825
|View full text |Cite
|
Sign up to set email alerts
|

Sensation seeking and its relationship with psychopathic traits, impulsivity and aggression: a validation of the Dutch Brief Sensation Seeking Scale (BSSS)

Abstract: Sensation seeking is a personality trait that manifests as a preference for change, variety and novelty. Sensation seeking has been positively associated with different externalising behaviours. However, its associations with psychopathic traits, impulsivity and aggression are unclear. These associations were examined via the psychometric properties of the Dutch version of the Brief Sensation Seeking Scale (BSSS) using individuals from the general population and forensic patients. The results show that the BSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…For example, some authors found, as in the present study, negative associations between psychopathic traits and both empathy components (Jonason & Kroll, 2015; Sellbom & Phillips, 2013), while others found that cognitive empathy was not significantly associated with psychopathic traits (Pajevic et al, 2018; Turner et al, 2019). These traits were also found to be positive predictors of impulsiveness and sensation seeking in some studies (van Dongen et al, 2021; Sellbom & Phillips, 2013; Weidacker et al, 2017) but not in others (Anderson et al, 2021; Gray et al, 2019). A possible explanation for these inconsistencies could be the lack of convergence between theoretical conceptualizations of psychopathic traits, measures (self‐reported scales or clinician‐rated measures), and research populations (students, community samples, offenders, etc.,) across studies (Burghart & Mier, 2022; Campos et al, 2022; Sellbom & Drislane, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, some authors found, as in the present study, negative associations between psychopathic traits and both empathy components (Jonason & Kroll, 2015; Sellbom & Phillips, 2013), while others found that cognitive empathy was not significantly associated with psychopathic traits (Pajevic et al, 2018; Turner et al, 2019). These traits were also found to be positive predictors of impulsiveness and sensation seeking in some studies (van Dongen et al, 2021; Sellbom & Phillips, 2013; Weidacker et al, 2017) but not in others (Anderson et al, 2021; Gray et al, 2019). A possible explanation for these inconsistencies could be the lack of convergence between theoretical conceptualizations of psychopathic traits, measures (self‐reported scales or clinician‐rated measures), and research populations (students, community samples, offenders, etc.,) across studies (Burghart & Mier, 2022; Campos et al, 2022; Sellbom & Drislane, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Impulsiveness and sensation seeking are personal dispositions that have also been studied in relation with psychopathic traits (Armstrong, Boisvert, Wells, & Lewis, 2020; Armstrong, Boisvert, Wells, Lewis, et al, 2020; Gray et al, 2019; Van Dongen et al, 2021). Impulsiveness is a multidimensional construct which predicts behaviors that appear to be ill‐considered, inconsiderably risky, inappropriate to the context, and often result in negative consequences (Billieux et al, 2012), while sensation seeking can be defined as the need to seek new, intense, and varied sensations and experiences, and the willingness to take risks (physical, financial, social, etc.,) to obtain such sensations (Zuckerman & Neeb, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The convenience sampling strategy is quick and cost effective but obviously results in sampling bias, limiting our ability to fully generalize the presented results. For example, a recent validation of the Dutch BSSS-8 scale reported an even higher discrepancy between the proportion of females and males [ 80 ]. Further research is required to thoroughly investigate the psychometric properties of the translated scale, using a more representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…Sensation Seeking was measured with the 8-item Brief Sensation Seeking Scale (BSSS). The internal consistency of this widely used test was adequate (Cronbach's a ¼ 0.73) (van Dongen, de Groot, Rassin, Hoyle, & Franken, 2022). Generalised Anxiety was measured with the 4-item version of the Generalised Anxiety Scale (GAD-7, a ¼ 0.76) (Spitzer, Kroenke, Williams, & L€ owe, 2006).…”
Section: Demographics and Personality Variablesmentioning
confidence: 99%